Metodología para el cálculo de la zona de cobertura de estaciones base de telefonía móvil de la red 4G, basada en la calidad y potencia de señal recibida (2023)
There is no doubt that everything that surrounds the human being is currently focused on technology, in this aspect communication plays a very important role due to the need for people, mobile devices, artificial intelligence systems, medical systems, among others, to remain permanently connected. One of these cases is reflected in much of the world's population, and is to be connected to mobile devices with internet access to interact remotely, to make a call, send a text message, download and upload files, among others.